Rutgers since 1945 : A History of the State University of New Jersey - Clemens, Paul G. E., 1947- (Book collections on Project MUSE., 2015)
"Spans the period from World War II to the present during which Rutgers grew from two small, liberal arts colleges, an agricultural school, and an engineering school into a major public research university. We chronicle the remarkable story of Rutgers's rise as a research university, but also the way the school has been experienced by generations or students and residents of the state. The Cold War, the student protests of the 1960s and the 1970s, the rise of identity politics on campus, big-time athletics, and the various ways students have shaped and been affected by popular culture all play a part in this story. Three chapters cover chronologically the major changes that occurred at the university between 1945 and the present, bringing up to date the work done in Richard P. McCormick's, Rutgers, A Bicentennial History (1966). The remaining chapters provide snapshots of some of the key themes in the contemporary history of the school -- campus life and campus activism, the school's growing strength as a research institution, the impact of Title IX on opportunities for women student athletes, the school's public presence as reflected in such long-standing institutions as the University Press, the Glee Club, and undergraduate journalism. Rutgers current residence halls, which house more students than at any other college in the nation, are the subject of a imaginatively illustrated, architectural analysis While much of the focus of our study is on the New Brunswick/Piscataway campus, attention has been paid throughout to Camden and Newark as well"--